Microsurgical tunica albuginea transplantation in an animal model - Salvatore Sansalone; Carla Loreto; Rosario Leonardi; Giuseppe Vespasiani; Giuseppe Musumeci; Claudia Lombardo; Sergio Castorina; Venera Cardile; Rosario Caltabiano (Asian Journal of Andrology, 2017)
Several andrological diseases require surgical repair or reconstruction of tunica albuginea, which envelops the corpora cavernosa penis. Despite intense research efforts involving a variety of biological materials, such as skin, muscle aponeurosis, human dura mater, tunica vaginalis, and pericardium, engineered tunica albuginea suitable for graft use is yet to be obtained. The study investigates microsurgical tunica albuginea allotransplantation in an animal model with the purpose of creation of an organ-specific tissue bank to store penile tissue, from cadaveric donors and male-to-female trans-sexual surgery, for allogeneic transplantation. Materials were tunica albuginea tissue explanted from 15 donor rats, cryopreserved at −80°C, gamma-irradiated, and implanted in 15 recipient rats, of which three rats were used as controls. Penile grafts were explanted at different time intervals; after macroscopic evaluation of the organ, the grafts were processed to morphological, histochemical, and immunohistochemical examinations by light microscopy. Detection of pro-inflammatory cytokines was also performed. Examination of the tunica albuginea allografts collected 1, 3, or 6 months after surgery and of control tunica albuginea fragments showed that tunica albuginea implants achieved biointegration with adjacent tissue at all-time points. The integration of cryopreserved rat tunica albuginea allografts, documented by our study, encourages the exploration of tunica albuginea allotransplantation in humans. In conclusion, the effectiveness and reliability of the tunica albuginea conditioning protocol described here suggest the feasibility of setting up a tunica albuginea bank as a further tissue bank.